Digital Innovation in Preserving Local Culture: Android-Based History Learning in Lubuklinggau City - Agus Susilo; Sariyatun Sariyatun; Muhammad Akhyar (Pascasarjana Universitas KH. Abdul Chalim, 2026)
preservation of local culture, particularly in the context of history education. This study aims to explore the role of Android-based history education in preserving local culture in Lubuklinggau and to reveal students' experiences in using it. The study uses a qualitative approach with data collection techniques through open questionnaires, interviews, and observations of high school students in Lubuklinggau City. The data were analyzed descriptively with an emphasis on interpreting students' experiences, perceptions, and responses to digital learning media. The results showed that the use of Android-based applications not only increased students' interest and motivation in learning history but also strengthened their understanding of local cultural values. Students felt that the learning was more contextual, interactive, and in line with the technological developments they use in their daily lives. In conclusion, Android-based digital innovation plays an important role in bridging the preservation of local culture with the needs of 21st-century education. The contribution of this study is to provide a new perspective on the integration of digital technology in local history learning that is relevant, meaningful, and supports the formation of students' cultural identity.